Interaction of mixing factors with mechanical properties of PP/ENR blend via response surface methodology / Noraiham Mohamad ... [et al.] - Mohamad, Noraiham (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2014)
This research is carried out to establish interaction between mixing parameters with mechanical properties of polypropylene (PP) incorporated with epoxidized natural rubber (ENR). The blends of PP/ENR were prepared by melt compounding using an internal mixer and vulcanized through sulfur curing system. The experiment was designed using two-level factorial design via response surface methodology by Design Expert software. Mechanical testing such as tensile test and impact test were performed to characterize the properties of PP/ENR blends. It was clearly observed that high ENR to PP ratio increases the toughness and flexibility of the PP/ENR blends. In comparison to the pure PP, PP/ENR blend with 40% ENR showed improvement of elongation at break and impact strength up to 68% and 56%, respectively. In contrary, the tensile strength and hardness decreases as the amount of PP decreases. The changes were associated to the properties imparted by the elastic chains of cross-linked ENR. The obtained properties showed good correlation with fracture surfaces observed in microscopy analysis performed by Field Emission Scanning Electron Microscope at magnifications of 500 and 5000-x.